Pattern of Oral Cancer between Smokers and Smokeless Tobacco Chewers in a Tertiary Care Hospital (Journal of Dentistry and Allied Science, 2024)
Background: Oral cancer is one of the most common cancers in Bangladesh and subcontinent region. In countries where tobacco consumption is common and had social recognition, there oral cancer shows the highest prevalence. In Bangladesh many people are under multiple risk factors of oral squamous cell carcinoma. The objective of this study is to evaluate the pattern of oral cancer between smokers and smokeless tobacco chewers and to see the association of oral cancer with smoking and smokeless tobacco habits. Methods: This cross-sectional, observational study was conducted in the Bangabandhu Sheikh Mujib Medical University, Dhaka. The study included 90 oral cancer patients who chewed smokeless tobacco or smoked. A detailed history was taken and relevant clinical examination was done regarding the variables of study. Data was analyzed to assess the pattern of oral cancer with the type of tobacco consumption. The descriptive and inferential statistics were calculated using SPSS software. Ethical clearance for the study was taken from institutional review board, BSMMU, Dhaka, Bangladesh. Results: Maximum patients (66.7%) were smokeless tobacco chewers. But, 24.4% patients were both smoker and smokeless tobacco chewers and 8.9% patients were only smoker. The most common habit of tobacco consumption in oral cancer patients was betel quid with zarda with gul (32.2%), followed by betel quid with zarda with sada pata (30.0%). Majority of the subjects reported with oral cancer at buccal mucosa (26.7%), followed by gingivobuccul sulcus (15.6%) and buccal mucosa with gingivobuccul sulcus (14.4%). Among the smokers maximum (37.5%) oral cancer involved the hard palate, followed by buccal mucosa (25.0%). Among the smokeless tobacco chewers, oral cancer involved mostly the buccal mucosa (30.0%) followed by in buccal mucosa with gingivobuccul sulcus (20.0%). Among smoker with smokeless tobacco chewers oral cancer involved the buccal mucosa (22.7%) followed by gingivobuccal sulcus (18.2%). Conclusion: According to this study, smokeless tobaccos alone or in association with smoking were observed as the main risk factors for oral cancer. Only smoking was observed as the less significant risk factors for oral cancer.Journal of Dentistry and Allied Science, Vol. 7 No 1: 8-15